AB0423 The threshold of pain in patients affected by rheumatoid arthritis correlates with ESR but not with ultrasound score. (23rd January 2014) - Talotta, R.; Miceli, G.; Bagnato, G.; Sangari, D.; Cassisi, D.; Corallo, G.; Tamburello, A.; Sarzi-Puttini, P.; Bagnato, G.
Abstract : Background: In clinical practice, joint synovitis is generally assessed indirectly, by collecting clinical and laboratory data. Ultrasound is a non-expensive, repeteable, non-invasive test and may help the clinician to monitor the response to the treatment with biologic and non-biologic DMARDs. Furthermore, ultrasound may detect cases of unsuspected inflammation even in those patients who have achieved clinical remission. Clinical judgment is largely based on self-assessment of disease activity, which is influenced in turn by patient's individual perception of pain, being pain the cardinal symptom of RA. Patients with high pain threshold may refer a low disease activity, even if laboratory and ultrasound prove otherwise. In fact, patients with long-standing RA, may develop adaptationt to pain, being capable to bear a major articular inflammation with less discomfort. Objectives: The aim of this study is to compare the variables used in clinical, serologic and ultrasonographic evaluation of patients with RA, including the measurement of pain threshold. Methods: We randomly enrolled 13 patients (11 females, 2 males) affected by RA treated with biological and non-biological DMARDs, referring to the UOC of Rheumatology of University Hospital of Messina. Mean age was 51, 6±11, 9 yrs and mean duration of disease was 11, 9±9, 4 yrs. Patients were assessed for tender and swollen joints, ESR, CRP, GH status, VAS disease and VAS pain. Hence we calculated DAS28, CDAI and SDAI. Meanwhile we assessed the degree of synovial effusion/synovitis and of Power Doppler vascularization using a semiquantitative scale (0-3 grades) on knees, wrists, 2°-3° metacarpophalangeal and 2°-3° proximal interphalangeal joints of both hands. Finally, we determined the pain threshold by applying a modified algometer on five body sites: wrist, ear lobe, biceps, pretibial area and calcaneal enthesis of the right side. Results: We do not found any correlation between the threshold of pain and the US score.On the contrary higher pain threshold was associated with an increase in ESR (p=0.04). No correlation was found between clinical evaluation and ultrasonography nor between clinical activity and algometer scores. Conclusions: These preliminary data show a significative correlation between pain threshold and ESR in patients with RA, indipendently from clinical assessment. As a higher algometer score may hide a flogistic condition, every RA patient shoud be tested for pain threshold. References: Aletaha D, Smolen JS. The Simplified Disease Activity Index and Clinical Disease Activity Index to monitor patients in standard clinical care. Rheum Dis Clin North Am 2009;35:759-72. Pollard LC, Ibrahim F, Choy EH et al. Pain thresholds in rheumatoid arthritis: the effect of tender point counts and disease duration. J Rheum 2012;39(1):28-31. Ozgocmen S, Ozdemir H, Kiris A et al. Clinical evaluation and Power Doppler sonography in rheumatoid arthritis: evidence for ongoing synovial inflammation in clinical remission. South Med J. 2008;101(3):240-5 Disclosure of Interest: None Declared